Komunikasi Internal dan Work-life Balance di Perusahaan Event Management - Hendrik, Hendrik; Utami, Lusia Savitri Setyo (Koneksi, 2025)
In recent decades, globalization and technological advancements have increased work pressures, blurring the boundaries between work and personal life. This highlights the importance of work-life balance in maintaining employee productivity. Effective internal communication within organizations directly impacts job satisfaction and the creation of work-life balance, especially in industries such as event management. PK Entertainment, a leading promoter in Indonesia, implements coordinated internal communication to ensure the smooth running of each stage of events. This study aims to explore and describe PK Entertainment's internal communication in fostering work-life balance. The concepts supporting this research include organizational communication, internal communication, organizational communication climate, and work-life balance. The researcher used a qualitative approach with a case study method. The findings show that transparency in internal communication allows employees to freely express opinions, supporting their personal development and skills. Leaders have a responsibility to ensure effective internal communication. Company support for work-life balance is crucial in creating a healthy work environment that enhances productivity and creativity. Internal communication plays a key role in creating productive collaboration, harmonious relationships, and building trust and motivation to achieve shared goals. Openness in the organizational communication climate creates a flexible, collaborative work environment that fosters work-life balance.  Dalam beberapa dekade terakhir, globalisasi dan kemajuan teknologi telah meningkatkan tekanan kerja, sehingga menghilangkan batas antara kehidupan kerja dan pribadi. Hal ini menekankan pentingnya work-life balance untuk menjaga produktivitas karyawan. Komunikasi internal yang efektif dalam organisasi berdampak langsung terhadap kepuasan kerja dan terciptanya work-life balance, terutama di industri hiburan seperti event management. PK Entertainment, sebagai promotor terkemuka di Indonesia, menerapkan komunikasi internal yang terkoordinasi untuk memastikan kelancaran setiap tahap acara. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan komunikasi internal PK Entertainment dalam menciptakan work-life balance. Konsep yang mendukung penelitian ini adalah konsep komunikasi organisasi, komunikasi internal, iklim komunikasi organisasi, dan work-life balance. Peneliti menggunakan pendekatan kualitatif dengan metode studi kasus. Hasil penelitian menunjukkan bahwa transparansi dalam alur komunikasi internal memungkinkan karyawan menyampaikan pendapat dengan bebas, mendukung pengembangan diri dan kemampuan mereka. Pemimpin memiliki tanggung jawab memastikan komunikasi internal berjalan baik. Dukungan perusahaan terhadap work-life balance sangat penting untuk membuat lingkungan kerja sehat yang meningkatkan produktivitas dan kreativitas. Komunikasi internal berperan dalam menciptakan kolaborasi produktif, hubungan harmonis, serta membangun kepercayaan dan motivasi dalam mencapai tujuan bersama. Keterbukaan dalam iklim komunikasi organisasi menciptakan lingkungan kerja yang fleksibel, kolaboratif, dan menciptakan work-life balance.